TINGKAT PENGETAHUAN DAN PERILAKU PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA KOMUNITAS PENGAMEN JALANAN - Angga Koswara; Sri Mulyanti; Ulfah Utami; Nurul Fatikhah (Poltekkes Kemenkes Bandung, 2022)
The Street Singers Group (KPJ) is an association of street singers who perform their musical performances in groups. At a young age, street buskers are always identified with all kinds of negative perspectives because they lead a very wild life. This study aims to determine the level of knowledge and behavior regarding dental and oral health maintenance in the Sky Music Street Singer Community, Bandung. The research method used is descriptive research. Sampling technique with cluster random sampling. Data collection in this study was conducted by means of interviews and google forms filled out by respondents. The results showed that respondents whose last education was junior high school had the least criteria 8 people with a percentage of 22.9%, respondents aged 15–24 years had less criteria as many as 9 people with a percentage of 25.8%, respondents who had negative behavior criteria as many as 23 people with a percentage of 66%, the factors that influence this are the level of education, information, environment and age. The level of knowledge and behavior in maintaining oral and dental health in the street busker community consists of 18 (51.5%) respondents having poor knowledge criteria, as many as 23 (66%) respondents having negative behavior criteria.